The development of green competency elements among polytechnic lecturers in Malaysia - M.Said, Salina; Hasan, Azman; Monzaid, Eza; Zaime, Adib Farhan (American Scientific Publishers, 2018)
This paper discusses the development of Green Competency Elements among Polytechnic lecturers in Malaysia. There are two purposes of this study, first is to establish the Green Competency Elements among Polytechnic lecturers as well as getting reliability for the element set. A qualitative approach using document analysis and experts interview protocol was conducted to form the Green Competency Elements among Polytechnic lecturers. Document analysis and expert interview data were analyzed manually using the matrix frequency table. Fleiss Kappa reliability analysis were used to determine the agreement index items for each of the elements identified. The reliability of the 4 elements and 17 sub elements that were established for Green Competency Elements among Polytechnic lecturers were tested using quantitative approach. To get the reliability for these elements, a cognitive test were distributed to 30 respondents. The findings of the Fleiss Kappa coefficient value was 0.98 (personal effectiveness), 0.95 (knowledge), 0.97 (skill) and 1.00 (sustainable practice) which showed almost perfect agreement. Responses analyzed using Rasch Model approach through Winsteps version 3.69.11 software came out with Alpha Cronbach values of 0.92 for the element formed. The development of Green Competency Elements among Polytechnic lecturers is one of the research efforts to enhance the competency of Polytechnic lecturers, especially in the aspect of personal effectiveness, knowledge, skill and sustainable practice. The outcome of this study will be one of the key elements for the development of Green Competency Model for Polytechnic lecturers.